The safety of bike share systems - Paul Schepers; Elliot Fishman (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2018)
This paper reviews available research on the safety impacts associated with the growth in bike share use. In the last 20 years the global fleet of dock-based and dockless bike share systems has grown to well over 4 500 000; making bike share one of the fastest growing modes of transport. This rapid increase in popularity has made bike safety a priority for policy makers and calls for a framework where bike share crash data is collected consistently to ensure safety risks can be identified and reduced, in order to encourage more sustainable urban mobility.
Keywords: 330